Cyclic nonlinear analysis of large-scale finite element meshes through the use of hybrid modeling (HYMOD) - Markou, George; Mourlas, Christos; Papadrakakis, Manolis (My University, 2017)
The simulation of multistory reinforced concrete structures through the use of 3D detail modeling approaches that account for cracking through the smeared crack approach, under ultimate limit state cyclic loading conditions, is currently an approach that is not available in any research or commercial software, due to the excessive computational demand that rises when dealing with this type of large-scale numerical models. Through this research work, the numerical results that were obtained through the use of the simplified hybrid modeling (HYMOD) approach are presented. HYMOD is used herein to illustrate the capabilities of the method in capturing the experimental results of a full-scale 4-storey RC building that was retrofitted with infill walls and carbon fiber polymer jacketing. The adopted modeling approach was found to be able to have a superior computational performance, thus being able to solve the at hand problem thousands of times in an affordable computational time. It is demonstrated that this type of analysis can provide with the ability to study the cyclic mechanical behavior of full-scale structures under ultimate limit state loading conditions, whereas will further utilize scientists to perform parametric investigations towards the optimum retrofitting design of RC structures at a large-scale numerical level.
Keywords: Hybrid finite elements; Cyclic loading; Retrofitting Walls; Large-Scale Numerical Problems